Prevalence of Factors Related to Cancer among Undergraduate Students in both Health and Life Sciences Areas - Silva, Christien Aurélio Lima de Oliveira da (2010)
The social and demographic transformations which Brazil has been going through have caused important changes in the morbidity and mortality profile, making cancer a public health problem. Approximately 489,270 new cases are estimated in Brazil in 2010. Knowing factors associated with cancer is essential to establish practices for health promotion and cancer prevention. This study aims to determine the prevalence of factors associated with cancer among graduate students in Health and Biology Sciences. A cross-sectional and descriptive study was conducted with participants of the Second Summer School for Oncology Research from INCA. Data on social and demographic variables, exposure to factors associated with cancer and health care were collected. The participants signed an informed consent and the study followed the guidelines of resolution 196/96. The population comprised 75% of women. Among the known risk factors for cancer development, a prevalence of 2,5% smokers, 12,5% risk consumers of alcohol, 51,3% sedentaries, 51,3% low fruits consumers, 40,0% low vegetables consumers, 60% low legumen consumers, 7,5% had sun exposure without the use of protective or filter, and 5,1% overweight were found. The high prevalence in some factors highlights the need to implement policies for prevention and health promotion in order to reduce the exposure of students of Health and Biological Sciences to factors associated with cancer.